Efforts To Improve Learning Outcomes For Creative Products And Entrepreneurship Through Problem Based Learning Model - Amri, Ahmad Risqie (Al'Adzkiya Journal, 2021)
This research is motivated by the value of student learning outcomes in learning Creative Products and Entrepreneurship. The teacher's lack of ability in designing and implementing methods, becomes an obstacle in the success of children in the learning process of mathematics. This research was conducted to improve student learning outcomes learning Creative Products and Entrepreneurship. The purpose of this study was to determine the increase in student learning outcomes towards learning Creative Products and Entrepreneurship.The research method used is classroom action research (Classroom Action Research), the research process is carried out in two cycles which previously carried out the cycle stage action, each cycle includes 4 stages, namely: 1) planning stage, 2) implementation stage, 3) observation stage, 4 ) reflection stage.